Iconografia de uma despedida: O adeus a Nelson Mandela por meio da charge - Dos Santos, Renata De Paula; Miani, Rozinaldo Antonio [UNESP] (Universidade Estadual de Londrina, 2015)
This article examines cartoons produced in South Africa as a posthumous tribute to Nelson Mandela. By analyzing the cartoon's discourse, we assess the popular leader of symbolic importance for national policy. We take as reference the concept of cartoon as a discursive and political characteristics, defended by Miani (2011) practice. Reflections on the South African historiography were developed from de Jonge (1991) and Marinovich and Silva (2003).
Iconography of a farewell: The goodbye to Nelson Mandela through cartoon
Keywords: Cartoon's discourse; Nelson mandela; South Africa